Leading extraordinarily positive performance - Cameron, Kim (Henry Stewart Talks, 2010)
Comparing positive leadership to normal leadership, The nature of abundance gaps, Studies confirming that a focus on abundance gaps leads to the heliotropic effect, Evidence of the impact of virtuousness on individual performance, Evidence of the impact of virtuousness practices on organizational performance, Discussion of the extraordinary case of the Rocky Flats Nuclear Arsenal, Resources for learning more
Reviewed at 2016/08/31